Mengembangkan Bakat Menulis Siswa, Meningkatkan Keterampilan Menulis Cerpen, Serta Menumbuhkan Minat Baca Dan Tulis - Ramlah HA. Gani; Nunung Supratmi; Titin Ernawati; Herman WIjaya (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
This community service is carried out to develop students ' writing talents, improve short story writing skills, and foster an interest in reading and writing. It aims to explain the importance of intensive training in writing short stories to awaken the literary talent of NWDI Pancor Kopong Junior High School students, which amounts to 15 people. The reason for choosing this topic is based on the awareness of the importance of developing creative writing skills in education and the recognition of the potential of literature as a means of self-expression and understanding that is important for the development of students. The approach used in the service is a training approach that includes the stages of planning, action, observation and reflection, and results. The planning stage includes the identification of students ' talents through questionnaires and interviews, as well as the preparation of training materials based on relevant literature. The action stage involves several weeks of intensive training focusing on developing the idea, drafting the plot, characterization and editing the script. Continuous observation is used to monitor the development of students ' skills, while the reflection stage evaluates the training results and designs improvements for the next stage. The evaluation results showed that this training was successful in improving students ' ability to develop short story ideas (80%), develop story plots (75%), describe character characters (85%), and edit scripts (70%). Further action plans include the refinement of training modules based on feedback and an increased focus on more in-depth writing techniques to ensure optimal achievement in the development of students ' literary talents.